2018
DOI: 10.1370/afm.2238
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Alcohol Consumption and Nocturnal Leg Cramps in Patients Over 60 Years Old: A Case-Control Study

Abstract: We identified an association between alcohol consumption and nocturnal leg cramps among patients aged 60 years and older attending general practices. These findings have implications for the prevention of cramps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…In order to explore the association between sedentary lifestyle and cramps, we compared (i) the "sedentary" group and the "very active" group, (ii) the "sedentary" group and the "moderately active" group and (iii) the "sedentary" group and the sum of both active groups with Bayesian univariate conditional logistic and hierarchic linear regressions to take into account the matching. Considering the strong association between the global alcoholic beverage consumption and nocturnal leg cramps 15 , we included the consumption of alcoholic beverage in a multivariate model. We then performed a conditional logistic regression to take the matching into account.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to explore the association between sedentary lifestyle and cramps, we compared (i) the "sedentary" group and the "very active" group, (ii) the "sedentary" group and the "moderately active" group and (iii) the "sedentary" group and the sum of both active groups with Bayesian univariate conditional logistic and hierarchic linear regressions to take into account the matching. Considering the strong association between the global alcoholic beverage consumption and nocturnal leg cramps 15 , we included the consumption of alcoholic beverage in a multivariate model. We then performed a conditional logistic regression to take the matching into account.…”
Section: Discussionmentioning
confidence: 99%
“…According to their DPAS, participants were distributed into three groups: (i) the "sedentary" group for a score between 0 and 10, (ii) the "moderately active" group between 11 and 20 and (iii) the "active to very active" group between 21 and 30. www.nature.com/scientificreports www.nature.com/scientificreports/ In a previous study, we identified an association between NLC and alcohol consumption among patients over 60 years old attending general practices 15 . In this study, we also used the E3N food frequency questionnaire to identify the consumption of alcoholic beverages 30,31 and distributed the participants into groups of consumers and non-consumers of alcoholic beverage (self-reported use in the past year).…”
Section: Data Collectionmentioning
confidence: 94%
See 1 more Smart Citation
“…7 Delacour et al find a strong association between alcohol consumption and leg cramps in general practice patients aged over 60 years. 8 They don't find a dose-response effect, but I wonder if the immediacy of leg cramps could be a motivator for some patients for whom the long-term effects of alcohol overuse are not compelling.…”
mentioning
confidence: 99%